Stratification strength and light climate explain variation in chlorophyll a at the continental scale in a European multilake survey in a heatwave summer - Daphne Donis; Evanthia Mantzouki; Daniel F. McGinnis; Dominic Vachon; Irene Gallego; Hans‐Peter Grossart; Lisette N. de Senerpont Domis; Sven Teurlincx; Laura Seelen; Miquel Lürling; Yvon Verstijnen; Valentini Maliaka; et al. (Limnology and Oceanography, 2021)
To determine the drivers of phytoplankton biomass, we collected standardized morphometric, physical, and biological data in 230 lakes across the Mediterranean, Continental, and Boreal climatic zones of the European continent. Multilinear regression models tested on this snapshot of mostly eutrophic lakes (median total phosphorus [TP] = 0.06 and total nitrogen [TN] = 0.7 mg L −1 ), and its subsets (2 depth types and 3 climatic zones), show that light climate and stratification strength were the most significant explanatory variables for chlorophyll a (Chl a ) variance. TN was a significant predictor for phytoplankton biomass for shallow and continental lakes, while TP never appeared as an explanatory variable, suggesting that under high TP, light, which partially controls stratification strength, becomes limiting for phytoplankton development. Mediterranean lakes were the warmest yet most weakly stratified and had significantly less Chl a than Boreal lakes, where the temperature anomaly from the long‐term average, during a summer heatwave was the highest (+4°C) and showed a significant, exponential relationship with stratification strength. This European survey represents a summer snapshot of phytoplankton biomass and its drivers, and lends support that light and stratification metrics, which are both affected by climate change, are better predictors for phytoplankton biomass in nutrient‐rich lakes than nutrient concentrations and surface temperature.

Fundamental niche prediction of the pathogenic yeasts Cryptococcus neoformans and Cryptococcus gattii in Europe - Massimo Cogliati; Erika Puccianti; Maria T. Montagna; Antonella De Donno; Serdar Susever; Cagri Ergin; Aristea Velegraki; Mohamed S. Ellabib; Simona Nardoni; Cristina Macci; Laura Trovato; Ludovico Dipineto; et al. (Environmental Microbiology, 2017)
Summary Fundamental niche prediction of Cryptococcus neoformans and Cryptococcus gattii in Europe is an important tool to understand where these pathogenic yeasts have a high probability to survive in the environment and therefore to identify the areas with high risk of infection. In this study, occurrence data for C . neoformans and C . gattii were compared by MaxEnt software with several bioclimatic conditions as well as with soil characteristics and land use. The results showed that C . gattii distribution can be predicted with high probability along the Mediterranean coast. The analysis of variables showed that its distribution is limited by low temperatures during the coldest season, and by heavy precipitations in the driest season. C . neoformans var. grubii is able to colonize the same areas of C . gattii but is more tolerant to cold winter temperatures and summer precipitations. In contrast, the C . neoformans var. neoformans map was completely different. The best conditions for its survival were displayed in sub‐continental areas and not along the Mediterranean coasts. In conclusion, we produced for the first time detailed prediction maps of the species and varieties of the C . neoformans and C . gattii species complex in Europe and Mediterranean area.